Foraging activity of the solitary andean bee, Anthophora walteri (Hymenoptera: Apidae, Anthophorini) - GONZALEZ, VÍCTOR H.; MANTILLA, BERNARDO; PALACIOS, ELIANA (Revista Colombiana de Entomología, 2006)
This note reports observations on the pollen collecting behavior and foraging activity of the solitary bee, Anthophora walteri Gonzalez on Salvia bogotensis in the Eastern Andes of Colombia. Bees foraged from 7:00–17:00 h, or when the temperature exceeded 15°C. Peak visits occurred between 8:00–9:00, when the temperature was about 18°C and the humidity was 60%. On average, bees spent 3 seconds at each flower and collected pollen throughout the day, although pollencollecting trips were twice as frequent in the morning as in the afternoon. The daily number and duration of foraging trips per bee ranged from 1–13 trips (x = 6.8 ± 4.3) and 4–88 min (x = 21.7 ± 23.8). Some possible morphological and behavioral adaptations for pollen collection on flowers of Salvia, as well as thermal constraints on the foraging activity of A. walteri in the Andes are also discussed.